Development and validation of the Chinese family environment influencing physical activity habits scale - Zhang, Xulin; Yan, Jingfei; Zhu, Weiqiang; Fu, Xiaoya (Frontiers in Psychology, 2024)
Introduction Adolescence represents a pivotal stage in the development of healthy behaviors, where establishing positive physical activity habits can have enduring effects on an individual's overall wellbeing. The ecological model highlights the influence of environmental factors on human behavior, with the family environment playing a significant role in shaping the physical activity habits of adolescents. Methods The aim of this scale is to develop a reliable and effective tool, customized for the unique societal context of China, to assess how family factors influence the physical activity habits of Chinese adolescents. Participants were recruited through stratified cluster sampling from 24 secondary schools in six Chinese provinces between October and November 2021, resulting in 1,061 participants. Analysis was conducted on 1,004 valid questionnaires, divided into two samples. Sample 1, consisting of 502 students (248 males and 254 females; Mage = 15.5), underwent item analysis and exploratory factor analysis. Sample 2, comprising 502 students (267 males and 235 females; Mage = 16.5), underwent confirmatory factor analysis and internal consistency reliability analysis. Results Through exploratory factor analysis, we extracted three factors comprising 15 items: “Family Environment Construction” (4 items), “Family Action Support” (6 items), and “Family Health Awareness” (5 items). The Cronbach's alpha values for these factors ranged from 0.890 to 0.894. Confirmatory factor analysis confirmed a satisfactory model fit (CMIN/DF = 1.45, SRMR = 0.027, GFI = 0.991, TLI = 0.989, RMSEA = 0.03). Discussion The scale demonstrated strong internal consistency and test-retest reliability, confirming its effectiveness in empirical research. This study holds significant implications for enhancing the physical activity levels of adolescents, promoting their physical and mental wellbeing, enriching their developmental experiences, and contributing to their overall sense of happiness.